AN ANALYSIS OF SLANG TRANSLATIONIN THE "JUNO" FILM: THE STRATEGIES AND REASONS - Ike Anggraeni, - (2010)
This paper presents an analysis of strategies used in translating the slang and the reasons that influence the use of slang words in the JUNO film. The reason of choosing the topic is because the existence of slang which is mostly used by teenager in the conversation. The aims of this study are investigating the translation strategies and types of slang. In the process of analyzing the data, there are some steps conducted by the writer. The first step is selecting the dialogue in the Juno film which contains of slang. Then, those dialogues are classified based on Willis' classification and Mattielo's classification of sociological properties. Afterward, each of slang in the dialogue of Juno film is analyzed by using Gottlieb's theory to uncover the subtitling strategies. Then, the writer finds out the reasons that influence the use of slang words in the "Juno" film. The result of the analysis is that the subtitler uses ten subtitling strategies. The biggest result of subtitling strategies is transfer. Regarding the findings and discussions, it can be concluded that there are 336 slang words. In this film, 57.73% of overall slang are those deriving new meaning from standard words, while 42.26% are those new invented words. This classification is proposed by Willis (1964: 195). The slang words in this film also are mostly appeared by Colour slang. The writer finds 78 items of Colour slang with the percentage 23.21% of the total data. Colour slang can make the speech more vivid, colourful and interesting. This type of slang is classified the slang based on sociological properties which is proposed by Mattielo (2008: 46). There are three reasons that influence the use of slang words in the "Juno" film. The first reason is that teenagers want to say something in a secret way. Second, teenagers want to show their anger by expressing it with slang words. The last is that teenagers want to have joy and get the laugh by using the slang. In conclusion, slang is not easy to be understood without recognizing the context. Therefore, the translator should find out the actual meaning of slang because there is some different understanding within different culture found in slang and even some slang meanings cannot be discovered in dictionaries.